2016
DOI: 10.1155/2016/5249013
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Malignant Biliary Obstruction with Severe Obesity Successfully Treated by Endoscopic Ultrasonography-Guided Biliary Drainage

Abstract: Here, we present a case of malignant biliary tract obstruction with severe obesity, which was successfully treated by endoscopic ultrasonography-guided biliary drainage (EUS-BD). A female patient in her sixties who had been undergoing chemotherapy for unresectable pancreatic head cancer was admitted to our institution for obstructive jaundice. She had diabetes mellitus, and her body mass index was 35.1 kg/m2. Initially, endoscopic retrograde cholangiopancreatography (ERCP) was performed, but bile duct cannulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…In a case report from Obana and Yamasaki of an obese patient (BMI: 35.1 kg/m 2 ) who underwent EUS-BD with the indication of difficult cannulation during ERCP, the bilirubin level clearly decreased from 14.1 mg/dL (before the procedure) to 2.3 mg/dL (after the procedure). The authors reported that EUS-BD could be performed successfully in this obese patient to achieve biliary drainage [ 15 ]. There have been no reports regarding the correlation of age or gender with the clinical success rate of the EUS-BD procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In a case report from Obana and Yamasaki of an obese patient (BMI: 35.1 kg/m 2 ) who underwent EUS-BD with the indication of difficult cannulation during ERCP, the bilirubin level clearly decreased from 14.1 mg/dL (before the procedure) to 2.3 mg/dL (after the procedure). The authors reported that EUS-BD could be performed successfully in this obese patient to achieve biliary drainage [ 15 ]. There have been no reports regarding the correlation of age or gender with the clinical success rate of the EUS-BD procedure.…”
Section: Discussionmentioning
confidence: 99%